The Physiological Response of Soybean Genotypes to VAM Inoculation on Selected Drought Stress Levels - HAPSOH HAPSOH; SUDIRMAN YAHYA; TEUKU MUHAMMAD HANAFIAH OELIM; BAMBANG SAPTA PURWOKO (Bogor Agricultural University, Indonesia, 2006)
Present research was aimed to study physiological changes of soybean which were inoculated with vesicular arbuscular mycorrhizal fungi (VAM). Glomus etunicatum was exposed to moderate and severe drought condition. Symbiotic association with VAM improved adaptability as it was shown by the increasing leaf proline content. The MLG 3474 and Sindoro are the more tolerant genotypes while the responses of plant to VAM on improving the adaptability to drought were larger on Lokon. Key words: Soybean, mycorrhiza, drought, proline